3D Compressible Navier-Stokes Equations Solve Optical Properties of Forced Shear Layers. (2017) - Tsai, Bor-Jang; Tsai, Yeong-Pei; Chou, Chung-Chyi; Ho, Yu-Tsung
Abstract: The optical properties of shear layers is a topic of research with applications in high power lasers and optical imaging systems. In recent years, it has been shown that large-scale structures are intrinsic features in a plane turbulent mixing layer. While there has been some research on the effects of turbulence on laser beams, there has been no study of the optical effects of large-scale structures as they exist in shear layer development, nor how these effects may be controlled. Since the susceptibility of a free shear layer to a forcing input increases as the location of the forcing moves closer to the trailing edge of the splitter plate. Disturbances can be imposed on shear layer using very small-amplitude displacements of the splitter-plate trailing edge in a direction perpendicular to the flow direction. We are studying the optical effects of large-scale structures in forced and unforced situations using periodic motion of a small flap at the trailing edge of the splitter plate. Three-dimensional Navier-Stokes equations in conservation law form are solved directly using the WENO scheme for the simulation of a spatially-developing free shear layer.